Influence of the social context in smoking during pregnancy - Lucíola D'Emery Siqueira; Lislaine Aparecida Fracolli; Sayuri Tanaka Maeda (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to know the social and family relationships of pregnant women and to analyze their influence in keep smoking during pregnancy. Method: it is a descriptive-exploratory study with a qualitative approach, which had as subjects 10 pregnant smokers. Data were collected from January to March / 2015, through interviews, and organized into graphical representations of the genogram/ecomap and discourse units. Results: pregnant women had low educational level, precarious insertion in the work market and relations of great dependence of the family. Tobacco consumption integrates the family environment and is viewed naturally in the sociocultural environment. In prenatal care, there was no coordinated and longitudinal intervention for smoking cessation. Conclusion: smoking cessation is strongly influenced by the social environment, and the family is an important component of this network. In this sense, strategies to approach smoking should allow a reflection of the norms and rules of the family.